Facile synthesis of glycerol carbonate via glycerolysis of urea catalysed by silicotungstates impregnated into MCM-41. Issue 65 (16th July 2015) - Narkhede, Nilesh; Patel, Anjali
<x xml:space="preserve">Abstract</x> The present contribution includes synthesis of glycerol carbonate over recyclable, silicotungstates anchored to MCM-41.